The Effects of Africa's Infrastructure Crisis and its Root Causes - THUSI, Xolani; MLAMBO, Victor H (International Journal of Environmental, Sustainability, and Social Science, 2023)
The development and expansion of any continent's economy is mostly dependent on the availability of world-class infrastructure capable of attracting international investors. The development and expansion of Africa's infrastructure is imperative; hence this will improve the African economy. The development and expansion of infrastructure improves the economy, resulting in many economic prospects for the inhabitants of any continent. However, in Africa, infrastructure development, investment, and preservation are among the lowest in the world. Infrastructure development will not only attract foreign investment and business, but it will also enhance trade between countries within the region. Trade between countries within the region is also heavily impacted by poor infrastructure investment in the continent, this puts much limit economic prospects within the region. This is a major concern; thus, Africa has several deficiencies in transport, telecommunications, water, health, and education infrastructures, all of which are crucial for Africa development. This is one of the main reasons why Africa has the highest levels of unemployment, poverty, food insecurity, migration, and poor education and health care systems. The author contends that investments and development in the African regional infrastructure are relatively low. This is a major barrier to regional economic development since the development of the region's economy relies on the development of infrastructure. This is unfortunate; hence, the region economy already lacks capabilities to provide the people with economic opportunities.  A qualitative method was used to investigate what is preventing infrastructure development in Africa and what this means for Africa as a developing continent.